2012
DOI: 10.1107/s1600536812026967
|View full text |Cite
|
Sign up to set email alerts
|

Tris(1,10-phenanthroline-κ2N,N′)iron(II) bis(1,1-dicyano-2-ethoxy-2-oxoethanide)

Abstract: The title compound, [Fe(C12H8N2)3](C6H5N2O2)2, consists of one [Fe(phen)3]2+ cation (phen = 1,10-phenanthroline) and two 1,1-dicyano-2-eth­oxy-2-oxoethanide anions. Five atoms of the anion are disordered over two positions [site occupancy = 0.521 (13) for the major component]. In the complex cation, the FeII atom is coordinated by six N atoms from three phen ligands in a distorted octa­hedral geometry. Two intra­molecular C—H⋯N hydrogen bonds occur in the complex cation. The crystal structure is mainly stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The average value of dihedral angle between pairs of phenanthroline planes is 82,1(3)°. The carbon-carbon and carbon-nitrogen intra-ring bond lengths agree with those observed in other metal complexes with chelating phen (Hoshina et al, 2000;Aparici Plaza et al, 2007;Cai & Zhan, 2012).…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…The average value of dihedral angle between pairs of phenanthroline planes is 82,1(3)°. The carbon-carbon and carbon-nitrogen intra-ring bond lengths agree with those observed in other metal complexes with chelating phen (Hoshina et al, 2000;Aparici Plaza et al, 2007;Cai & Zhan, 2012).…”
Section: Methodssupporting
confidence: 85%
“…Comment 1,10-Phenanthroline (phen) is a widely utilized chelating ligand in coordination chemistry and a lot of complexes with phen as a ligand have been reported (Hoshina et al, 2000;Hwang & Ha, 2006;Zhou & Guo, 2007). Recently, Cai et al (2012) has reported the structure of a complex with [Fe(phen) 3 ] 2+ as cation and 1,1-dicyano-2-ethoxy-2-oxoethanide as counter-ion. We report here the synthesis and crystal structure of the title compound, in which a polynitrile anion acts as counter-ion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation